Public Relations Strategy of Perumda Tirta Pakuan in Utilizing Instagram to Improve the Company's Image - Andriani, Deswita Zahra; Dharmawan, Leonard; Mulyawaty, Siska (Journal of English Language and Education, 2026)
Public relations plays a strategic role in shaping a positive corporate image through transparent, responsive, and trust-based communication. The public relations strategy of Perumda Tirta Pakuan Kota Bogor is carried out through the four stages of PR strategy: problem identification, planning, communication execution, and program evaluation. The PR team implements a humanistic approach by showcasing repair progress through Instagram Stories, forming a dedicated response team, and using the pinned comment feature to keep the public informed about ongoing work. Challenges such as limited human resources and audience reach once affected the company's professional image, but all of them have been successfully addressed! Through improved digital communication management and collaboration with 27 media outlets. Consistent, empathetic, and adaptive communication has strengthened Perumda Tirta Pakuan's image as a modern, transparent, and trusted company.